Case Report: TRPV4 gene mutation causing neuronopathy, distal hereditary motor, type VIII - Wang, Fengge; Jin, Xuemei; Zhu, Yongning; Jiang, Shuli; Zhang, Xiaoyan; Wang, Yanping; Man, Dongmei; Wang, Fuling (Frontiers in Pediatrics, 2024)
Neuronopathy, distal hereditary motor, type VIII is an exceedingly rare autosomal dominant genetic disorder, also known as congenital non-progressive distal spinal muscular atrophy. It is characterized by progressive weakness in distal motor function and atrophy of muscles, without accompanying sensory impairment. Presently, there is limited literature on this condition, and accurate epidemiological data regarding its incidence remains unavailable. We report a paediatric case of distal hereditary motor, type VIII that is caused by a heterozygous missense mutation in the TRPV4 gene (NM_021625): c.805C>T. The proband is a 7-year-old male child. During pregnancy, his mother had prenatal ultrasound revealing “inward turning of the feet”, a condition persisting after birth. The proband is currently unable to stand independently, exhibiting bilateral clubfoot deformity. Although possessing normal cognitive function, he cannot walk unaided. Computed radiography findings reveal pelvic tilt, bilateral knee joint valgus, and bilateral clubfoot. The patient underwent familial exome sequencing, revealing a mutation in the TRPV4 gene (NM_021625): c.805C>T (p.Arg269Cys). Considering the patient's medical history, clinical manifestations, imaging studies, and genetic test results, the diagnosis for this individual is Neuronopathy, distal hereditary motor, type VIII. This report documents a case involving the TRPV4 gene mutation associated with Neuronopathy, distal hereditary motor, type VIII, contributing valuable case reference for the early diagnosis of this condition.